2010
DOI: 10.1136/tc.2009.034512
|View full text |Cite
|
Sign up to set email alerts
|

Associations between adolescent socioeducational status and use of snus and smoking

Abstract: Adolescents' socioeducational status was associated with smoking for boys and girls, while there was no similar association with snus use. This may indicate that snus truly deviates from how smoking is distributed across social strata or that snus is at a much earlier stage in the social diffusion process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 27 publications
5
31
1
Order By: Relevance
“…An explanation might be the high prevalence of snus use among men in Norway and Sweden [29,30], which may be a substitute for both occasional and daily smoking. One should also note that the snus users represent a more resourceful group (by having higher social status and/or higher education) than the daily smokers [31]. Further, a previous study from Norway reported that a combination of daily snus use and nondaily smoking among men was common [26].…”
Section: Discussionmentioning
confidence: 99%
“…An explanation might be the high prevalence of snus use among men in Norway and Sweden [29,30], which may be a substitute for both occasional and daily smoking. One should also note that the snus users represent a more resourceful group (by having higher social status and/or higher education) than the daily smokers [31]. Further, a previous study from Norway reported that a combination of daily snus use and nondaily smoking among men was common [26].…”
Section: Discussionmentioning
confidence: 99%
“…Test market surveys indicate that the product has substantial potential for attracting users [2], and early figures suggest that 29% of young male adults have tried snus during the last year [3]. Snus has been widely available for decades in Sweden and Norway, but its use has increased further in later years, particularly among young adults [4,5], so that in both these countries snus use is now about as common as smoking among men. In young women, prevalence of snus use has increased from negligible levels to near 5% in a few years [4,5].…”
Section: Introductionmentioning
confidence: 97%
“…Snus has been widely available for decades in Sweden and Norway, but its use has increased further in later years, particularly among young adults [4,5], so that in both these countries snus use is now about as common as smoking among men. In young women, prevalence of snus use has increased from negligible levels to near 5% in a few years [4,5]. In light of the increasing prevalence of snus use where it is available, and its introduction to new markets, research on snus use and health becomes increasingly relevant.…”
Section: Introductionmentioning
confidence: 98%
“…However, without neglecting the powerful impact of parental SES, indicators such as adolescent educational aspiration, educational achievement or the type of school attended may more accurately describe adolescents’ current and future SES [22,23,24]. Studies that directly compared the impact of various SES measures on adolescent smoking behaviour suggest that parental SES indicators seem to be less strongly associated with adolescent smoking behaviour than are adolescent SES indicators [11,13,15,23,24,25,26,27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%